Restoration of quinine-stimulated Fos-immunoreactive neurons in the central nucleus of the amygdala and gustatory cortex following reinnervation or cross-reinnervation of the lingual taste nerves in rats - King, Camille Tessitore (2014)
Remarkably, when lingual gustatory nerves are surgically re-routed to inappropriate taste fields in the tongue, some taste functions recover. We previously demonstrated that quinine-stimulated oromotor rejection reflexes and neural activity (assessed by Fos-immunoreactivity) in subregions of hindbrain gustatory nuclei were restored if the posterior tongue, which contains receptor cells that respond strongly to bitter compounds, was cross-reinnervated by the chorda tympani nerve. Such functional recovery was not seen if instead, the anterior tongue, where receptor cells are less responsive to bitter compounds, was cross-reinnervated by the glossopharyngeal nerve, despite that this nerve typically responds robustly to bitter substances. Thus, recovery depended more on the taste field being reinnervated than on the nerve itself. Here, the distribution of quinine-stimulated Fos-immunoreactive neurons in two taste-associated forebrain areas was examined in these same rats. In the central nucleus of the amygdala (CeA), a rostrocaudal gradient characterized the normal quinine-stimulated Fos response, with the greatest number of labeled cells rostrally situated. Quinine-stimulated neurons were found throughout the gustatory cortex but a ‘hot spot’ was observed in its anterior-posterior center in subregions approximating the dysgranular/agranular layers. Fos neurons here and in the rostral CeA were highly correlated with quinine-elicited gapes. Denervation of the posterior tongue eliminated, and its reinnervation by either nerve restored, numbers of quinine-stimulated labeled cells in the rostral-most CeA and in the subregion approximating dysgranular gustatory cortex. These results underscore the remarkable plasticity of the gustatory system and also help clarify the functional anatomy of neural circuits activated by bitter taste stimulation.